Luminescence of Baikal water as a dynamic background of the Baikal-GVD Neutrino Telescope. (29th November 2021) - Allakhverdyan, V.A.; Avrorin, A.D.; Avrorin, A.V.; Aynutdinov, V.M.; Bannasch, R.; Bardačová, Z.; Belolaptikov, I.A.; Borina, I.V.; Brudanin, V.B.; Budnev, N.M.; Dik, V.Y.; Domogatsky, G.V.; et al.
Abstract: The Baikal-GVD is a neutrino telescope situated in the deepest freshwater lake in the world — Lake Baikal. The design of the Baikal-GVD trigger system allows also to study the ambient light of the lake. The analysis of the optical light activity of Baikal water, particularly, time and spatial variations of the luminescence activity for data collected in years 2018, 2019, and 2020 is presented. For the first time we observed highly luminescent layer moving upwards with maximal speed of 28 m/day in January 2021.